Application of recombinant latex allergens in diagnostics of occupational latex allergy - Ewa Nowakowska-Świrta; Marta Wiszniewska; Jolanta Walusiak-Skorupa (Nofer Institute of Occupational Medicine, 2015)
Over many years, allergy to natural rubber latex has been a major problem among health care workers (HCW). The diagnosis of occupational allergy requires methods of high diagnostic accuracy in view of certification implications (e.g., a sick worker quits a job). With the development of molecular methods, the frequency of application of recombinant allergens in the diagnostics of allergic diseases continues to increase. This paper reviews the applicability of laboratory tests which use recombinant allergens in the diagnostics of occupational allergy. The diagnosis of latex allergy is based on the presence of clinical symptoms linked with exposure to latex allergens, positive skin prick tests and detection of specific IgE antibodies to latex in serum. Moreover, in some cases specific challenge tests are conducted. The analysis of literature indicates that applying the panel of recombinant latex allergens in diagnostic tests, cross-reactivity can very likely be excluded and/or sensitization can be confirmed without the need for specific challenge tests, which in case of latex allergens carries a potential risk of generalized reactions. Med Pr 2015;66(1):85-97